2013
DOI: 10.1007/s00405-013-2358-7
|View full text |Cite
|
Sign up to set email alerts
|

Safety of intralesional cidofovir in patients with recurrent respiratory papillomatosis: an international retrospective study on 635 RRP patients

Abstract: Intralesional use of cidofovir (Vistide(®)) has been one of the mainstays of adjuvant therapy in patients with recurrent respiratory papillomatosis (RRP) since 1998. In 2011, a communication provided by the producer of cidofovir addressed very serious side effects concerning its off-label use. As this was a general warning, it was inconclusive whether this would account for its use in RRP. The aim of this study is to determine whether nephrotoxic, neutropenic, or oncogenic side effects have occurred after intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 34 publications
4
21
0
1
Order By: Relevance
“…Although there were some anecdotal reports documenting serious adverse reactions in RRP in off-label use of CDV (Tjon Pian Gi et al, 2012), a multicentre retrospective chart review involving 16 hospitals from 11 countries worldwide with 635 RRP patients (of whom 275 were treated with CDV) was performed. In this study, no clinical evidence was found for more long-term nephrotoxicity, neutropenia or laryngeal malignancies after intralesional administration of CDV (Tjon Pian Gi et al, 2013). In another recent study, it was concluded that CDV remains the leading option for adjuvant treatment of patients with RRP of all ages whose disease is difficult to manage with surgery alone.…”
Section: In Vitro In Vivo and Clinical Evidences For The Anti-papillmentioning
confidence: 86%
See 2 more Smart Citations
“…Although there were some anecdotal reports documenting serious adverse reactions in RRP in off-label use of CDV (Tjon Pian Gi et al, 2012), a multicentre retrospective chart review involving 16 hospitals from 11 countries worldwide with 635 RRP patients (of whom 275 were treated with CDV) was performed. In this study, no clinical evidence was found for more long-term nephrotoxicity, neutropenia or laryngeal malignancies after intralesional administration of CDV (Tjon Pian Gi et al, 2013). In another recent study, it was concluded that CDV remains the leading option for adjuvant treatment of patients with RRP of all ages whose disease is difficult to manage with surgery alone.…”
Section: In Vitro In Vivo and Clinical Evidences For The Anti-papillmentioning
confidence: 86%
“…CDV represents an option to reduce the risks of frequent surgical debulking and airway obstruction in children and adults with recurrent or severe disease (Derkay et al, 2013). CDV is nowadays recognized as an adjuvant therapy for the management of this disease (Tjon Pian Gi et al, 2013;Graupp et al, 2013). A type specific real-time PCR to measure HPV6 and HPV11 DNA loads in patients with recurrent respiratory papillomatosis treated with CDV, indicated that the drug significantly reduced viral load following intralesional application (Mikolajczak et al, 2012).…”
Section: In Vitro In Vivo and Clinical Evidences For The Anti-papillmentioning
confidence: 98%
See 1 more Smart Citation
“…Laryngologists from all 16 participating hospitals from 11 countries of the international multicentre study by Tjon Pian Gi et al . were invited to participate in this retrospective international multicentre study.…”
Section: Methodsmentioning
confidence: 99%
“…The role of cidofovir in the therapy of recurrent laryngeal papillomatosis has not yet been sufficiently evaluated. Several studies have shown that when locally applied, cidofovir is virustatic without any side effects and, in particular, is able to significantly reduce the rate of recurrence [12,13]. The importance of evaluating the impact of any disease on the patient's quality of life and the outcome of various therapeutic interventions is increasing.…”
Section: Discussionmentioning
confidence: 99%